Pre- and Post-partum Berberine Supplementation in Dairy Goats as a Novel Strategy to Mitigate Oxidative Stress and Inflammation - Ghavipanje, Navid; Fathi Nasri, Mohammad Hasan; Farhangfar, Seyyed Homayoun; Ghiasi, Seyyed Ehsan; Vargas-Bello-Pérez, Einar (Frontiers in Veterinary Science, 2021)
As in dairy cattle, goats during the transition period face risk factors, in particular negative energy balance (NEB), inflammation, and impairment of the antioxidant response. The current study determined the effects of pre- and post-partum berberine (BBR) supplementation on antioxidant status and inflammation response during the transition period in dairy goats. Twenty-four primiparous Saanen goats were randomly divided into four groups: control (CON, without BBR) and supplemented with 1 g/day BBR (BBR1), 2 g/day BBR (BBR2), or 4 g/day BBR (BBR4). The blood samples were collected weekly from 21 days pre-partum to 21 days post-partum. Compared with CON, supplementation with either BBR2 or BBR4 decreased (P ≤ 0.05) the levels of plasma non-esterified fatty acids (NEFA) at kidding and thereafter an increased (P ≤ 0.05) the plasma levels of glucose and insulin. Following BBR ingestion, blood antioxidant status elevated throughout the transition period, so that total antioxidant capacity (TAC), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), and catalase activity were increased (P ≤ 0.05) and plasma malondialdehyde (MDA) was decreased (P ≤ 0.05). Likewise, paraoxonase (PON) was reduced (P ≤ 0.05) in goats fed BBR2 and BBR4. The levels of haptoglobin, ceruloplasmin, and bilirubin were reduced (P ≤ 0.05) by BBR2 and BBR4 immediately before kidding and thereafter. The results demonstrated that supplementation of either 2 or 4 g/day BBR enhanced antioxidant capacity and immune function of transition goats and improved post-partum performance showing its beneficial effect to mitigate oxidative stress and inflammation during the transition period in dairy goats.